Prediksi Gaya Belajar Selmes Melalui Kemampuan Berpikir Aljabar Menggunakan Analisis Diskriminan Linear - Rashieka Widyarini Suryoputro; Karunia Eka Lestari; Ekasatya Aldila Afriansyah (FKIP Universitas Mataram, 2026)
Learning styles can be associated with mathematical abilities, particularly algebraic thinking ability, where variations in students abilities may indicate differences in their learning styles. This study aims to predict Selmes learning styles based on algebraic thinking ability using Linear Discriminant Analysis (LDA). This research employed a quantitative approach conducted among 7th and 8th grade students at SMP Islam Teratai Putih Global. The sample consisted of 57 students selected using a simple random sampling technique. The research instruments included an algebraic thinking ability test and the Selmes learning style questionnaire, which classified into five categories: surface, deep, hard work, organisation, and motivation. The data were analyzes using LDA to predict students learning styles according to Selmes theory based on their algebraic thinking ability. The result showed that the model generated discriminant functions and posterior probability that were used to determine prediction outcomes. Furthermore, the test results indicated that the discriminant model was statically significant in predicting Selmes learning styles based on algebraic thinking ability. The model performance evaluation demonstrated that the model achieved relatively good performances in terms of accuracy, macro average precision, and macro average F1-Score. However, the macro average recall indicated that the model performance still requires further improvement.